Inducible nitric oxide synthase enhances disease aggressiveness in pancreatic cancer - Wang, Jian; Gaida, Matthias (OncoTarget, 2016)
Oncotarget | https://doi.org/10.18632/oncotarget.10323 Jian Wang, Peijun He, Matthias Gaida, Shouhui Yang, Aaron J. Schetter, Jochen Gaedcke, B. Michael Ghadimi, Thomas Ried, Harris Yfantis, Dong Lee, Jonathan M....